HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN KONTROL KESEHATAN DALAM PENCEGAHAN KOMPLIKASI AKIBAT HIPERTENSI DI DESA LICIN - Mummar, Fathan (2023)
Background: Hypertension is one of the diseases which is a problem for health all over the world and cannot be cured, so that people with hypertension must always comply with health checks so as not to cause complications. In health checks family support has a very important role and a healthy family will be achieved with the support provided by the family. However, in reality there are still families who do not provide full support so that people with hypertension are not compliant in health control. The purpose of this study was to analyze the relationship between family support and health control adherence in preventing complications in Licin Village. The research method used in this study is quantitative correlation through a cross-sectional approach with data collection techniques using instruments in the form of questionnaires and then analyzed using the Spearman Rank test. The research sample was 101 people using simple random sampling technique. The results of the study showed that there was a relationship between family support and health control adherence in preventing complications due to hypertension in Licin Village because the p value <α value (0.000 <0.05). This relationship is shown by the correlation coefficient value of 0.689 which is included in the strong category (0.51-0.75), because the coefficient value (r) is positive, the relationship has a unidirectional meaning, meaning that the better the family support given, the higher the compliance control of hypertension sufferers. In conclusion, this study shows that there is a relationship between family support and compliance with health controls. The recommended suggestions are that families can provide support to people with hypertension in increasing compliance with health controls.